2007
DOI: 10.1016/j.catena.2006.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vegetation recovery on water erosion at short and medium-term after experimental fires in a Mediterranean shrubland

Abstract: This paper reports the influence that vegetation recovery has exerted on the soil behaviour to erosion by water during both the first and eight years after experimental fires. The work was carried out at La Concordia Experimental Station (Valencia, Spain), which includes nine plots (4 m wide x 20 m long) installed on a calcareous hillside representative of Mediterranean shrubland areas. In June 1995 a set of experimental fires were carry out at two intensity levels (high and moderate) with three plots replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 30 publications
(39 reference statements)
3
45
0
8
Order By: Relevance
“…While, in periods II and IV those thresholds were 3.4 mm h -1 for runoff and 4.6 mm h -1 for soil losses. -García et al (2007) observed that, in the experimental station, and one year after the former experimental fires in 1995, a 77% more runoff was produced in the burnt plots than in the control ones: 19.4 L m -2 yr -1 in T1, 14.7 L m -2 yr -1 in T2, and 3.8 L m -2 yr -1 in T3.…”
Section: Rainfall Characteristicsmentioning
confidence: 89%
See 3 more Smart Citations
“…While, in periods II and IV those thresholds were 3.4 mm h -1 for runoff and 4.6 mm h -1 for soil losses. -García et al (2007) observed that, in the experimental station, and one year after the former experimental fires in 1995, a 77% more runoff was produced in the burnt plots than in the control ones: 19.4 L m -2 yr -1 in T1, 14.7 L m -2 yr -1 in T2, and 3.8 L m -2 yr -1 in T3.…”
Section: Rainfall Characteristicsmentioning
confidence: 89%
“…In T1 and T2, the post-fire regenerated biomass reached 0.5 and 0.4 kg m -2 , respectively (Gimeno-García et al, 2007), an enough quantity of biomass to set a date for a repeated fire impact. On the other hand, the percentage of vegetation cover before 2003 fires was 30 35% in T1 and T2, and 45% in T3.…”
Section: Fire Experimental History and Designmentioning
confidence: 98%
See 2 more Smart Citations
“…However, it is noteworthy that in most cases plant recovery is rapid, with regrowth of shrub and herbaceous cover again protecting the soil within several months (Cerdà, 1998;Cerdà and Lasanta, 2005;Gimeno-García et al, 2007;Wittenberg and Inbar, 2007). Ruiz-Flaño et al (1992) and hydrological responses (Beguería et al, 2003), and reduces sediment yield, although other problems can become evident.…”
Section: Badlands and Forest Fires: The Face Of The Mediterranean?mentioning
confidence: 99%